Enterovirus serotypes in patients with central nervous system and respiratory infections in Viet Nam 1997-2010 - B'Krong, N; Minh, N; Qui, P; Chau, T; Nghia, H; Do, L; Nhung, N; Van Vinh Chau, N; Thwaites, G; Van Tan, L; van Doorn, H; Thanh, T (BioMed Central, 2018)
Background: Enteroviruses are the most common causative agents of human illness. Enteroviruses have been associated with regional and global epidemics, recently, including with severe disease (Enterovirus A71 and D68), and are of interest as emerging viruses. Here, we typed Enterovirus A-D (EV) from central nervous system (CNS) and respiratory infections in Viet Nam. Methods: Data and specimens from prospective observational clinical studies conducted between 1997 and 2010 were used. Species and serotypes were determined using type-specific RT-PCR and viral protein 1 or 4 (VP1, VP4) sequencing. Results: Samples from patients with CNS infection (51 children – 10 CSF and 41 respiratory/rectal swabs) and 28 adults (28 CSF) and respiratory infection (124 children – 124 respiratory swabs) were analysed. Twenty-six different serotypes of the four Enterovirus species (A-D) were identified, including EV-A71 and EV-D68. Enterovirus B was associated with viral meningitis in children and adults. Hand, foot and mouth disease associated Enteroviruses A (EV-A71 and Coxsackievirus [CV] A10) were detected in children with encephalitis. Diverse serotypes of all four Enterovirus species were found in respiratory samples, including 2 polio-vaccine viruses, but also 8 CV-A24 and 8 EV-D68. With the exception of EV-D68, the relevance of these viruses in respiratory infection remains unknown. Conclusion: We describe the diverse spectrum of enteroviruses from patients with CNS and respiratory infections in Viet Nam between 1997 and 2010. These data confirm the global circulation of Enterovirus genera and their associations and are important for clinical diagnostics, patient management, and outbreak response.